Analisis Kebijakan Pengelolaan dan Budidaya Ekosistem Gambut di Indonesia - Penerapan Pendekatan Advocacy Coalition Framework - Bergas Chahyo Baskoro; Cecep Kusmana; Hariadi Kartodihardjo (Institut Teknologi Sepuluh Nopember, 2018)
Indonesia has become the fourth largest owner of peat reserves in the worldafter Canada, Russia and the United States. Peatlands play a major role ascarbon sinks and maintain a hydrological system. The destructive andoxidized characteristics of peat make the International and IndonesianGovernments pay high attention to the management and protection of peatecosystems. Through the Advocacy Coalition Framework (ACF) approach,this study found that there are a variety of actors and stakeholders whoinfluence the dynamics of peat management and cultivation policyformulation in Indonesia. The actors and stakeholders formed a coalition bycarrying out the logic of their respective belief systems, namely: Coalition Awhich has a belief system that peat land is a potential resource developed forcultivation and Coalition B which has a belief system that views peatecosystems as vulnerable ecosystems that must be protected and rehabilitated.The results of this study are expected to be able to provide recommendationsneeded in realizing sustainable management of peat ecosystems.